Investigação da capacidade intelectiva de pacientes pediátricos diagnosticados com tumores de fossa posterior - Garcia, Danielle Ferreira (2011)
Central Nervous System are the most common pediatric solid tumors. 60% of these tumors arise in posterior fossa, mainly in cerebellum. The first therapeutic approach is surgical resection. Malignant tumors require additional strategies - chemotherapy and radiotherapy. The increasing survival evidences that childhood brain tumors result in academic and social difficulties that compromise the quality of life of the patients. This study investigated the intellectual functioning of children between 7 to 15 years diagnosed with posterior fossa tumors and treated at CEHOPE - Recife / PE. 21 children were eligible - including 13 children with pilocytic astrocytoma (G1) who underwent only surgery resection, and eight children with medulloblastoma (G2) - submitted to surgical resection, chemotherapy and craniospinal radiotherapy. Participants were evaluated by the Wechsler Intelligence Scale for Children - WISC-III. Children of G1 scored better than children of G2. Inferential tools (Mann-Whitney Ü Test) identified significant diferences (p ≤ 0.05) between the Performance IQ (PIQ) and Processing Speed Index (PSI) as a function of treatment modality; Full Scale IQ (FSIQ), PIQ and PSI as a function of parental educational level; PIQ, FSIQ, IVP and Freedom from Distractibility (FDI) as a function of time between diagnosis and evaluation. These results showed the late and progressive impact of radiotherapy on white matter and information processing speed. Furthermore, children whose parents have higher educational level showed better intellectual performance, indicating the influence of xxii socio-cultural variables on cognitive development. The impact of cancer and its treatment on cognitive development and learning should not be underestimated. These results support the need to increase the understanding of such effects in order to propose therapeutic strategies which ensure that, in addition to the cure, the full development of children with this pathology